Transcriptome Concordance Between Borderline Tumors and Endometrioid Carcinoma: An Integrative Genomic Analysis - Mio Takahashi; Kohei Nakamura; Tatsuyuki Chiyoda; Chihiro Okada; Sachio Nohara; Reika Takamatsu; Shintaro Yanazume; Hiroaki Kobayashi; Hiroshi Nishihara; Wataru Yamagami (Cancer Medicine)
ABSTRACT Background Borderline ovarian tumors (BOTs) differ from ovarian carcinomas in their clinical presentation and behavior, yet their molecular characteristics remain poorly understood. This study aims to address this gap by integrating whole‐exome sequencing (WES) and RNA sequencing (RNA‐seq) to compare BOTs with high‐grade serous carcinoma (HGSC), endometrioid carcinoma (EC), and clear‐cell carcinoma (CCC). Objective To elucidate the molecular features of BOTs and evaluate their similarities and differences in comparison to HGSC, EC, and CCC. Methods The study analyzed 44 ovarian tumor samples, employing WES to identify genomic alterations and RNA‐seq to examine transcriptomic profiles. Comparative analyses were conducted to investigate the molecular relationships among the tumor types. Results The genomic analysis revealed that BOTs share significant similarities with EC. Furthermore, the transcriptomic data highlighted a novel and substantial similarity between BOTs and EC, suggesting deeper biological linkages, including potentially shared oncogenic pathways or tumor microenvironmental factors. These findings challenge traditional classifications and suggest a closer molecular alignment of BOTs with EC than previously understood. Conclusions This study provides new insights into the molecular characteristics of BOTs, demonstrating their significant resemblance to EC at both the genomic and transcriptomic levels. These results underscore the potential need to reconsider the molecular classification of ovarian tumors and open new avenues for research into the pathogenesis and treatment strategies for BOTs.